Road infrastructure concession practice in Europe - Bousquet, Franck (Policy research working paper, 2001)
Europe has a wealth of experience with motorway concessions and the issues associated with concession contracts and other infrastructure funding systems, toll charges and other parts to remuneration, and risk sharing between concession authorities and concession companies